Analisis Strategi Pemasaran Usaha Kerajinan Tangan Dalam Upaya Meningkatkan Penjualan Guna Meningkatkan Perekonomian Masyarakat (Studi Kasus Kendang Djimbe UD Fajar Jaya Blitar) - Fahinda Rio Dinata; Rois Arifin; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to determine the marketing strategy that can be used in the handicraft business of Kendang Djimbe UD Fajar Jaya based on a SWOT analysis in increasing sales volume. This type of research is qualitative research. The analytical method used in this research is SWOT analysis. The population in this study is the owner of the Kendang Djimbe handicraft business UD Fajar Jaya. Sources of data used in this study are primary data and secondary data. The results of this study indicate (1) In the S-O strategy, what UD Fajar Jaya can do is to carry out a system of purchasing and stocking raw materials. (2) In the W-O strategy, what UD Fajar Jaya can do is take advantage of the availability of materials to make other products. (3) In the ST strategy, what UD Fajar Jaya can do is utilize the quality of raw materials and finished products. (4) In the W-T strategy, what UD Fajar Jaya can do is to innovate and design products. Keywords: Marketing Strategy, SWOT Analysis and Sales Volume